Quantum Dot Solar Cells: Small Beginnings Have Large Impacts - Ganesan, Abiseka Akash; Houtepen, Arjan J.; Crisp, Ryan (Applied Sciences, 2018)
From a niche field over 30 years ago, quantum dots (QDs) have developed into viable materials for many commercial optoelectronic devices. We discuss the advancements in Pb-based QD solar cells (QDSCs) from a viewpoint of the pathways an excited state can take when relaxing back to the ground state. Systematically understanding the fundamental processes occurring in QDs has led to improvements in solar cell efficiency from similar to 3% to over 13% in 8 years. We compile data from similar to 200 articles reporting functioning QDSCs to give an overview of the current limitations in the technology. We find that the open circuit voltage limits the device efficiency and propose some strategies for overcoming this limitation.
Keywords: quantum dots; lead sulfide; solar cells; photovoltaics; IV-VI semiconductors; nanocrystals; solution-processed; ligand-exchange